The gold cartel government intervention in gold, the mega-bubble in paper, and what this means for your future - Speck, Dimitri (Houndmills Palgrave Macmillan, 2013)
In times of financial crises and imminent sovereign defaults, gold is the investment on everyone's lips. As a safe investment, one could traditionally rely on gold markets for good, stable performance, however in recent years, they have seen surprising volatility and price fluctuation, with no visible reason as to why.
Includes bibliographical references and index.
Keywords: Gold--Economic aspects